The production of broad-spectrum antibiotics from phytopathogen Epicoccum sorghinum by culturing in host edible mushroom Thelephora ganbajun extract. (August 2022) - Wang, Cui-Fang; Yang, Xue-Qiong; Shi, Wen-Zhi; Long, Xing; Su, Shuang; Cen, Rong-Huan; Yang, Ya-Bin; Ding, Zhong-Tao
Abstract: Metabolism of special endophytes and phytopathogens can be induced by the symbiotic interactions with the host. A phytopathogen Epicoccum sorghinum cultured in host mushroom Thelephora ganbajun medium exhibited different metabolites compared with that of ordinary medium. An unprecedented scaffold possessing the same substructure as perylenequinone mycotoxin, a first methyl rearrangement product of phytotoxin, epoxydon 6-methylsalicylate ester, three undescribed compounds, and an undescribed natural product were isolated from E. sorghinum cultured in T. ganbajun . Episorin A and epicosorin A were produced from E. sorghinum induced by culturing in host medium. Episorin A was the first example of perylenequinone analogue in the natural products. These induced compounds and other metabolites showed notable antibiosis against endogenous fungi, and insect existing in mushroom. Induced episorin A showed significant inhibitory effects on nitric oxide production in LPS-activated macrophages, and anti-acetylcholinesterase with the IC50 at 5.40 ± 0.25  μ M, and 4.32  μ M, respectively, and cytotoxicity against HL-60, A-549, SMMC-7721, MCF-7 and SW480 with IC50 at 14.21 ± 0.53, 17.93 ± 0.22, 18.17 ± 0.63, 28.36 ± 0.43, and 18.20 ± 1.03  μ M. Graphical abstract: Image 1 Highlights: Six undescribed compounds were found from culture of Epicoccum sorghinum in Thelephora ganbajun medium. The inducing novel antibiotic, episorin A indicated significant activities. The interaction of host and endogenous fungi can induce the production of novel antibiotics.